Anaesthesia in abalone, Haliotis midae - White, Hermien Ilse (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1996)
The principle aim of this study was to isolate a chemical for the "safe anaesthesia" of abalone under commercial farming conditions. "Safe anaesthesia" implied that the anaesthetic had no immediate detrimental or long term sublethal effect on the abalone, that it was safe for the farmer, the consumer and the environment. Four chemicals, magnesium sulphate (MgS0â‚„), ethylenediamine tetra-acetic acid (EDTA), 2-phenoxyethanol and procaine hydrochloride were shown to effectively inhibit the in vitro contraction of isolated tarsal muscle of Haliotis midae. This identified them as potential anaesthetics for abalone. Since abalone, like any other aquaculture species, would be subject to frequent size-sorting during the grow-out period, size related dosage tables were developed for the four chemicals at a temperature of 18â °C. Dosage tables were also developed for benzocaine and carbon dioxide (C0â‚‚), Three size classes (5-15, 20-50 and 60-90 mm shell length (SL)) of abalone were considered. Only three of the six chemicals, viz. MgS0â‚„, 2-phenoxyethanol and COâ‚‚, met the criteria of an effective abalone anaesthetic in that they effected rapid and mortality-free anaesthesia. The other three chemicals caused mortalities and were considered to be unsuitable for commercial scale anaesthesia. Temperature related dosage tables were then developed for MgS0â‚„ and COâ‚‚, MgS0â‚„ concentrations and COâ‚‚ flow rates for effective anaesthesia in abalone were found to be inversely related to temperature. The three size classes of H. midae were intermittently exposed to MgS0â‚„ and 2-phenoxyethanol anaesthesia for an eight month period to determine the effect of the anaesthetics on growth rate. Because of an increased resistance to the efficacy of 2-phenoxyethanol and high monthly mortalities it was concluded that this chemical was unsafe and unsuitable for commercial use. MgS0â‚„, on the other hand, had no effect on growth of abalone and no significant effect on the rate of mortality. MgS0â‚„ also had no measurable effect on H. midae muscle ultrastructure and, by implication had no effect on flesh texture. The use of MgS0â‚„ as an anaesthetic would, therefore, not affect marketability. Moreover, no magnesium residues were found in H. midae muscle tissue after short term or intermittent long term exposure to MgS0â‚„ anaesthesia. It was found that the three size classes of H. midae used in this study could be safely exposed to the recommended MgS0â‚„ concentrations for up to 40 minutes without any mortalities. This is more than adequate for routine farming procedures. Medium size abalone (20-50 mm SL) were also safely exposed to 14 g.100 mlâ »Â¹ MgS0â‚„ for up to 6 hours without any mortalities. The results have shown that MgS0â‚„ was undoubtedly the best chemical that was evaluated for anaesthesia of H. midae in this study. It fulfils the requirements set forth by the U.S.A. Food and Drug Administration (FDA) in that it is safe for the abalone, the farmer, the consumer and the environment.
Keywords: Abalones; Animal anesthesia